2009
DOI: 10.1002/jmor.10806
|View full text |Cite
|
Sign up to set email alerts
|

Sperm ultrastructure of the spider crab Maja brachydactyla (Decapoda: Brachyura)

Abstract: This study describes spermatogenesis in a majid crab (Maja brachydactyla) using electron microscopy and reports the origin of the different organelles present in the spermatozoa. Spermatogenesis in M. brachydactyla follows the general pattern observed in other brachyuran species but with several peculiarities. Annulate lamellae have been reported in brachyuran spermatogenesis during the diplotene stage of first spermatocytes, the early and mid-spermatids. Unlike previous observations, a Golgi complex has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
69
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 49 publications
5
69
0
Order By: Relevance
“…This reduction has also been observed in other crab species such as Ucides cordatus (Linnaeus, 1763) and in particular, in portunids such as C. sapidus, P. pelagicus and C. danae (Johnson, 1980;Castilho et al, 2008;Stewart et al, 2010;Ravi et al, 2012;Zara et al, 2012). However, in Maja brachydactyla Balss, 1922 no nuclear reduction was observed during spermiogenesis (Simeó et al, 2010). Callinectes ornatus did not show a difference between spermatogonia and primary spermatocytes, although the cells were smaller, differing from C. danae (Zara et al, 2012).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…This reduction has also been observed in other crab species such as Ucides cordatus (Linnaeus, 1763) and in particular, in portunids such as C. sapidus, P. pelagicus and C. danae (Johnson, 1980;Castilho et al, 2008;Stewart et al, 2010;Ravi et al, 2012;Zara et al, 2012). However, in Maja brachydactyla Balss, 1922 no nuclear reduction was observed during spermiogenesis (Simeó et al, 2010). Callinectes ornatus did not show a difference between spermatogonia and primary spermatocytes, although the cells were smaller, differing from C. danae (Zara et al, 2012).…”
Section: Discussionsupporting
confidence: 54%
“…This crab supports an important smallscale fishery, as a bycatch of shrimp fishing (Severino-Rodrigues et al, 2001), and shows reproductive system. The male reproductive system has been studied in some brachyurans, including Portunidae (Cronin, 1947;Johnson, 1980;Stewart et al, 2010), Ucididae (Castilho et al, 2008), Eriphiidae (Erkan et al, 2009), Geryonidae (Hinsch and McKnight, 1988), Cancridae (Moriyasu et al, 2002), Grapsidae (Garcia and Silva, 2006), Epialtidae (Hinsch and Walker, 1974;Sal Moyano et al, 2009), Oregoneiidae (Beninger et al, 1988;Moriyasu and Benhalima, 1998;Sainte-Marie and Sainte-Marie, 1999), Inachidae (Diesel, 1989) and Majidae (Simeó et al, 2009(Simeó et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Niksirat et al (2014b) found that membranous lamellae detach from the cell after release of spermatozoa from the spermatophore. Simeó et al (2010) reported a similar region in the spermatozoa of spider crab Maja brachydactyla, called the SO-complex, consisting of membranes, mitochondria and occasionally microtubules. The origin of such complexes is usually considered to originate from the nuclear envelope, endoplasmic reticulum or Golgi apparatus Langreth, 1969;Reger, 1970;Kang et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Apart from its taxonomic and phylogenetic importance, knowledge of spermatozoal morphology can contribute to understanding the complex mechanisms of acrosome reaction and gamete fertilization (Simeo et al, 2010). The acrosome complex and nucleus are located at the anterior and posterior of the crayfish spermatozoon, respectively.…”
Section: Biology Of Gametes In the Crayfishmentioning
confidence: 99%